Intoxicación infantil por medicamentos: experiencias de las madres que acudieron a un hospital público de II nivel en Bogotá D.C.-Colombia. - Flórez Buitrago, Astrid Catalina
The present research was directed with the objective of getting to know the experience that mothers of children below or equal to five years of age had when their offspring got intoxicated with medication. From oral account by carers, the research focused on the associated conditions, care at home, reasons to visit the hospital, medication storage and precautions taken in order to avoid further similar situations. Information was obtained from a second level hospital data bases located in Ciudad Bolívar locality. This was done during 2015-16. Five families were contacted and interviewed at their homes for data recollection. Results allow to conclude that intoxication events are mostly registered by adult women and relatives; intoxication associated conditions are: easy-access to medication, colorful medication containers and flavorful medication, absence of carers. Among the measures taken to control the situation at home –identified after the intoxication event- there are various actions, such as providing the child with water to produce vomit, the request of help and the transportation of the patient to the hospital. Usually, carers showed knowledge regarding intoxication, adverse effect and impact on their children’s health -in the case they had not received proper attention- as a result of several pedagogical lectures given by Secretaría de Salud on this respect. From the results, we can conclude that it is necessary to enhance data bases from the children carers; carers must provide real and reliable information on identification documents and location of children’s places of residence. Collective simple and standardized strategies should be designed and offered by Secretaría de Salud and educational institutions in order to prevent accidents and verify medication conditions, storage and elimination. A follow up of these processes and the cases studied in the present investigation should be done.